Biotechnology regulation in a developing country context: the role of scientists - Kingiri, A. N. (In Conference on Agro-Biotechnology, Biosafety and Seed Systems in Developing Countries, 2011)
Scientists for a long time have been associated with the role of generating the evidence-base and reliable knowledge that ultimately informs public policy with a view to ensure evidence-based and/or research-informed policy decisions. However, recent demands for accountability in management of controversies associated with biotechnology have created a new platform for experts in biotechnology research and regulation. This has challenged the previously undisputed knowledge production role with the public demanding to be part of the biotechnology governance and policy decision-making process. The role of scientists in biotechnology regulation in practice is investigated using Kenya Biosafety Act formulation process and implementation as a case study. Based on interview data solicited from different stakeholders who participated in the process, this paper exposes challenges that exist when scientists get entangled in public policy formulation process due to the underlying value based practices. It appeals for reflexivity in order for the process to accommodate different values and interests towards a biotechnology development for the benefit of the poor.